ANALISIS PENERAPAN LAPORAN KEUANGAN BERDASARKAN PEDOMAN AKUNTANSI PESANTREN MENGGUNAKAN PSAK NO.45 - Yulian Sahri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Finance is one of the factors that helps boarding schools succeed in their development efforts, since the financial field aids in the management of education. To preserve public trust in financial management, transparency and publishing in the form of presentation of financial statements in compliance with standards are required. It will also provide contributors a sense of security because they believe their donations have been properly managed. As professional organizations of accountants and architects of financial accounting standards in Indonesia, Bank Indonesia and the Indonesian Institute of Accountants collaborated on the development of the Pesantren Accounting Guidelines, a financial reporting guide for boarding schools. The Financial Accounting Standards of Entities Without Public Accountability are the subject of this accounting guideline (SAK ETAP). Financial Position Report, Activity Report, Cash Flow Statement, and Notes on Financial Statements are the components of Pondok Pesantren financial statements based on pesantren accounting rules. This is a descriptive study that employs a mixed-methods approach (mixed methods). This study employs a mix of research methodologies (mixed methods), in which researchers employ both qualitative and quantitative methodologies in their investigation. Financial reports based on Islamic Boarding School Accounting Guidelines have not been given by Al-Manar Muhammadiyah Islamic Boarding School and The lack of understanding of financial statement preparation on the part of the Islamic boarding school, as well as the lack of information and socialization related to the Accounting Guidelines for Islamic Boarding Schools